Perspective of Total Quality Management and its Effect on the Performance of 2nd Stage of Primary Education Schools: A Field in Lattakia - Tayoub, mahmoud; Darwish, Ramadan; Husien, Mahmoud Hasan (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التعرف على نظام إدارة الجودة الشاملة وأثره على أداء مدارس التعليم الأساسي (ح2) من خلال تحسين أساليب وطرق العمل, استخدام فرق العمل, تحقيق رضا المستفيدين, إكساب العاملين مهارات الأداء الجيد في العمل, خدمة المجتمع المحلي, ولتحقيق أهداف البحث تمّ بناء استبانة, وتوزيعها على عينة من المديرين والمعلمين, وانتهى البحث إلى النتائج الآتية: 1- وجود درجة عالية من الوعي لدى المديرين, ودرجة مقبولة لدى المعلمين حول مدى تطبيق نظام إدارة الجودة الشاملة وأثره على أداء مدارس التعليم الأساسي (ح2). 2- وجود فروق ذات دلالة إحصائية بين متوسطات استجابات المديرين والمعلمين حول مدى تطبيق نظام إدارة الجودة الشاملة وأثره على أداء مدارس التعليم الأساسي فيما يتعلق باستخدام فرق العمل, وإكساب العاملين مهارات الأداء الجيد في العمل, وهذه الفروق تعود للمديرين. This research aims to identify the total quality management system and its effect on the performance of 2nd Stage of Primary Education School through enhancing the ways and methods of performance, use of teamwork, achieving the satisfaction of the beneficiaries, getting the workers acquire the good performance skills in work, serving the local society, and to achieve the research objectives, a questionnaire was prepared and applied on a sample of Directors and teachers. The research concluded to the following results: 1- There is a higher degree of the directors’ awareness, and acceptable one of the teachers’ awareness about system application of total quality management and its effect on the performance of 2nd Stage of Primary Education Schools. 2- There are statistically significant differences between the means of directors’ and teachers’ answers about the extent of system application of total quality management and its effect on the performance of 2nd Stage of Primary Education Schools concerning the teamwork and getting the workers acquire the good performance skills in work. These differences were related to the directors.